2014
DOI: 10.1371/journal.pone.0113258
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Splice-Site Mutation in ALS2 Establishes the Diagnosis of Juvenile Amyotrophic Lateral Sclerosis in a Family with Early Onset Anarthria and Generalized Dystonias

Abstract: The diagnosis of childhood neurological disorders remains challenging given the overlapping clinical presentation across subgroups and heterogeneous presentation within subgroups. To determine the underlying genetic cause of a severe neurological disorder in a large consanguineous Pakistani family presenting with severe scoliosis, anarthria and progressive neuromuscular degeneration, we performed genome-wide homozygosity mapping accompanied by whole-exome sequencing in two affected first cousins and their unaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
0
18
1
Order By: Relevance
“…The novel phenotype of JALS/ALS2 associated with generalized dystonia has previously been reported in two unrelated consanguineous families of Bangladeshi and Turkish descent, with homozygous loss of function variants in ALS2 [26]. Shortly thereafter, the same phenotype was described in a large consanguineous Pakistani family with a homozygous splice site variant in ALS2 [27]. Other novel clinical findings in the Bangladeshi family described in the first paper [26] include microcephaly and cerebellar signs, but the authors noted that it is unclear whether these features are caused by the ALS2 pathogenic variant.…”
Section: Discussionmentioning
confidence: 61%
“…The novel phenotype of JALS/ALS2 associated with generalized dystonia has previously been reported in two unrelated consanguineous families of Bangladeshi and Turkish descent, with homozygous loss of function variants in ALS2 [26]. Shortly thereafter, the same phenotype was described in a large consanguineous Pakistani family with a homozygous splice site variant in ALS2 [27]. Other novel clinical findings in the Bangladeshi family described in the first paper [26] include microcephaly and cerebellar signs, but the authors noted that it is unclear whether these features are caused by the ALS2 pathogenic variant.…”
Section: Discussionmentioning
confidence: 61%
“…In the typical adult onset ALS, Alsin gene is rarely mutated [ 30 ]. Recently, a novel splice-site mutation (c.3512 + 1G > A) in Alsin was identified in a consanguineous JALS family with early onset anarthria and generalized dystonia [ 31 ].…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…Mutations in the Alsin gene cause three distinct disorders: infantile ascending hereditary spastic paraplegia (IAHSP), juvenile primary lateral sclerosis (JPLS), and autosomal recessive juvenile amyotrophic lateral sclerosis (JALS) (Table 1 ) [ 8 , 9 ]. A recent study reported patients with ALS2 with nonsense and frameshift mutations in the Alsin gene who presented with generalized dystonia and cerebellar signs [ 10 ]. Although the phenotype-genotype correlation remains undetermined so far, most of the mutations predict truncated proteins, which could be unstable in structure and lose their function.…”
Section: Classification Of Hereditary Alsmentioning
confidence: 99%